Corporate blended learning in Portugal: current status and future directions - Marçal, J. (2014)
The aim of this study is to characterize the current status of blended learning in Portugal, given that b-learning has grown exponentially in the Portuguese market over recent years. 38 organizations (representing 68% of all institutions certified to provide distance training by the Government Labour Office – DGERT -) participated in this study. The results revealed that in 2007, although the predominant instructional format in Portugal was still face-to-face training (65%), e-learning at 15% came in behind b-learning with 20%. Data also revealed that 50% of distance training department coordinators believe that b-learning produces better training outcomes than face-to-face training alone, when considering the same content and learning objectives. Furthermore, when comparing b-learning and e-learning outcomes with similar content and learning objectives, 78.1% of these coordinators declared that b-learning produces better outcomes than e-learning alone. Hence, the content analysis indicated positive perceptions with regard to the future direction of b-learning, leading to the conclusion that in the long-term, corporate b-learning training will develop considerably in this country.